Some Weighted Inequalities for Higher-Order Partial Derivatives in Two Dimensions and Its Applications - Erden, Samet; Sarikaya, M. Zeki (IndoMS, 2020)
We establish some Ostrowski type inequalities involving higher-order partial derivatives for two-dimensional integrals on Lebesgue spaces (L_âˆž, L_p and Lâ‚). Some applications in Numerical Analysis in connection with cubature formula are given. Finally,Â with the help of obtained inequality, we establish applications for the kth moment of random variables.